DINAMIKA IZIN PENGELOLAAN PERTAMBANGAN MUHAMMADIYAH: KAJIAN FIKIH EKOLOGI - Luthfiah, Siti; Wijayanti, Anisa; Ramadhan, M. Syafrie; Zayyanurroihan, Maris; Reziana, Bella (Smart Education, 2025)
Abstract: This article explores the social and religious dynamics that have emerged following the government’s issuance of mining management permits to religious organizations, with a spesicific focus on Muhammadiyah. The study employs a qualitative approach using library research and content analysis methods, concentrating on three main areas: first, public responses both supportive and critical that have surfaced on social media; second, the perspective of Islamic ecological jurisprudence (fiqh al-bi’ah) on the exploitation of natural resources; and third, the concrete steps taken by Muhammadiyah in reflecting ecological jurisprudence in its approach. The findings indicate that, despite notable public resistance, Muhammadiyah does not simply abandon Islamic foundational values in accepting the mining concession. Through the five principles of maqasid al-shari’ah and institutional strategies such as the formation of professional business entities, Muhammadiyah strives to develop an ethical ad responsible model for resource management. Keyword: islamic ecological jurisprudence;mining;religious organizations;public controversy. Abstrak: Artikel ini mengkaji dinamika sosial dan keagamaan yang muncul pasca-pemberian izin usaha pertambangan oleh pemerintah kepada ormas keagamaan, dengan fokus khusus pada Muhammadiyah. Kajian ini menggunakan pendekatan kualitatif dengan metode kepustakaan dan analisis isi, dengan fokus pada tiga bidang utama: pertama, tanggapan masyarakat yang mendukung maupun mengkritik yang mengemuka di media sosial; kedua, perspektif fikih ekologi Islam (fiqh al-bi’ah) tentang eksploitasi sumber daya alam; dan ketiga, langkah konkret yang ditempuh Muhammadiyah dalam merefleksikan fikih ekologi dalam pendekatannya. Temuan penelitian menunjukkan bahwa, meskipun ada penolakan dari masyarakat, Muhammadiyah tidak serta merta meninggalkan nilai-nilai dasar Islam dalam menerima konsesi pertambangan. Melalui lima prinsip maqasid al-shari’ah dan strategi kelembagaan seperti pembentukan badan usaha profesional, Muhammadiyah berupaya mengembangkan model pengelolaan sumber daya yang etis dan bertanggung jawab. Kata kunci: yurisprudensi ekologi islam, pertambangan, organisasi keagamaan, kontroversi publik.